The impact of miR-21 on epithelial intercellular junctions influencing gut inflammation and barrier integrity - Mercurio, Kevin Jay Belarmino (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2026)
MicroRNAs (miRNAs) are short nucleotides that bind to seed regions in target mRNA and impact protein synthesis. These molecules have emerged as a diverse set of regulators for the immune response during inflammation. One such category of immune dysregulation studied in conjunction with miRNAs is inflammatory bowel disease (IBD) like Crohns disease or ulcerative colitis, characterized by debilitating chronic inflammation along regions of the gastrointestinal tract. During the inflammatory response, intestinal epithelial cells (IECs) react to changes in the gut environment which can impact gut permeability via intercellular junctions. These responses can be regulated by miRNAs such as miRNA-21 (miR-21). Previous work from the Corr group identified a novel role for miR-21, whereby loss of miR-21 protects against development of colitis in mice by inducing health-promoting microbiota. However, the molecular mechanisms underlying this phenotype, particularly the mechanisms by which miR-21 negatively regulates mucosal barrier permeability, remain to be elaborated. Therefore, this thesis addressed the knowledge gap by which miR-21 influences gut barrier integrity and susceptibility to intestinal inflammation. Among the major barrier components, intercellular junctions govern integrity by dictating transport, adhesion and communication between IECs. Most research focuses on associations between these junctions and IBD activity, which lack mechanistic understanding of their roles during inflammation. Here, in vivo and in vitro approaches were used to expand on the mechanistic impacts miR-21 has on intercellular junctions and cellular processes connected to these entities. This work demonstrated that miR-21 deficiency results in differential expression of adherens junction (AJ) and tight junction (TJ) components within whole colon tissue and colon IECs from miR-21-/- mice compared to wild type (WT) under healthy conditions. Furthermore, the DSS-induced colitis model for acute IBD as well as a DSS recovery model using miR-21-/- mice were utilized to investigate the impact of miR-21 expression on the mucosal barrier, particularly the regulation and integrity of junctional complexes. This work found that gene expression of the major epithelial AJ component E-cadherin showed a consistent negative association with miR-21 levels in the DSS recovery model, along with the increase of fragmented E-cadherin protein and localization to the top of distal colon crypts during miR-21 deficiency. With the regulation of E-cadherin involved in epithelial wound healing, further investigations using the human adenocarcinoma cell line Caco-2 transfected with miR-21 modulators were conducted during TNF--induced inflammation. This work showed that miR-21 directly targets E-cadherin and acts as a fine-tuner for regulating both activators and inhibitors of epithelial wound healing processes like TGF- signalling. Another integral component of gut barrier permeability is the TJ protein claudin-4, also showed induced expression during miR-21 deficiency. Here, this work showed that expression of claudin-4 was consistently altered in vivo at the mRNA and protein level in miR-21-/- mice. These observations suggest a novel link between miR-21 and shared TJ regulators among foundational cellular processes such as vesicular trafficking via the Golgi. Indeed, miR-21 levels were shown to positively associate with components of the retrograde transport pathway in miR-21-/- tissue of the DSS recovery model, and their localization to the Golgi in vitro during TNF--induced inflammation. Lastly, this work highlighted the importance of epithelial-specific expression of miR-21. Regulation of these pathways and the resulting mucosal barrier for disease susceptibility was assessed through the in-house creation of an IEC-specific conditional knockout of miR-21 (miR-21IEC-KO). This strain has initiated the discovery of novel IEC-specific pathways by which miR-21 impacts overall gut homeostasis, contributing to the pathophysiology of intestinal inflammation. Notably, this work will enhance our understanding of mucosal barrier regulation and contribute to the development of new therapeutic strategies for the treatment of chronic diseases like IBD.
APPROVED
Keywords: inflammatory bowel disease; microRNA; miR-21; intercellular junction; adherens junction; tight junction